Experimental Investigation of Shear Behavior and Pore Structure Evolution in Heat-Treated Granite Subjected to Liquid Nitrogen and Water Cooling - Fan Zhang; Shengyuan Liu; Subiao Zhang; Yiming Zhang; Shaohui Quan; Man Li (Applied Sciences)
It is imperative to understand the shear mechanical properties and pore evolution of granite under thermal shock to assess the fracturing of hot dry rock reservoirs. In this study, variable-angle shear tests were performed on coarse- and fine-grained granite samples following liquid nitrogen (LN2) cooling under different high-temperature conditions. The effect of thermal treatment temperature, particle type, and cooling method on the shear strength, cohesion, and angle of internal friction of granite was then analyzed. To this end, low field nuclear magnetic resonance (NMR) and scanning electron microscopy (SEM) were used to investigate the pore size distribution and microstructural evolution of granite. The experimental results indicate that both the shear strength and cohesion of granite initially increase and then decrease with the rise in thermal treatment temperature. The maximum increases in shear strength and cohesion are 38.0% and 36.7%, respectively, while the maximum decreases reach 43.7% and 42.4%. Notably, the most pronounced thermal hardening effect is observed at 200 °C. In contrast, the internal friction angle exhibits a decreasing-then-increasing trend as the temperature rises, with a maximum reduction of 5.4% and a maximum increase of 14.5%. In addition, fine-grained granite exhibits superior shear strength and a more pronounced thermal hardening effect compared to coarse-grained granite. Furthermore, the damage effect caused by thermal shock increases with increasing heat treatment temperature, with the damage effect induced by liquid nitrogen cooling being particularly significant compared to water cooling. Furthermore, for both types of granite at the same shear angle, an increase in the heat treatment temperature results in a corresponding increase in the total fracture area, with the fracture area after liquid nitrogen cooling being more significant. The macroscopic failure mode changes from a mixed compression–shear failure mode to a direct shear failure mode with increasing shear angle. NMR testing shows that liquid nitrogen cooling can effectively increase the proportion of medium pores and large pores in the granite and increase the connectivity of internal pores; specifically, in coarse-grained granite, medium pores and large pores collectively increased by 10.5%, while in fine-grained granite, the total increase in medium pores reached 51%. As the heat treatment temperature increases, the type of crack that develops in granite changes from intragranular to transgranular. In addition, the fracture surface of granite is more prone to form micropores and small pores when cooled with liquid nitrogen, increasing the connectivity of the crack network. The results of this research will be useful for fracturing hot dry rock reservoirs.